2004
DOI: 10.1007/s00442-004-1548-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of omnivorous crayfish in littoral communities

Abstract: Large omnivorous predators may play particularly important roles determining the structure of communities because of their broad diets and simultaneous effects on multiple trophic levels. From June 2001 to June 2002 we quantified community structure and ecosystem attributes of six newly establishing freshwater ponds (660 m2 each) after populations of omnivorous crayfish (Orconectes virilis) were introduced to three of the ponds. Crayfish preyed heavily on fish eggs in this experiment, which reduced recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 47 publications
2
105
0
5
Order By: Relevance
“…Through a combination of large size, broad feeding habitats and high densities attained, their introduction to new habitats can have a significant impact on the aquatic environment (NYSTRÖM and STRAND, 1996;NYSTRÖM, 2002;DORN and WOJDAK, 2004). The introduction of North American crayfish species into Europe has been partially responsible for severe declines in indigenous European species (HENTTONEN and HUNER, 1999;HOLDICH, ROGERS and REYNOLDS, 1999) through a combination of transfer of crayfish plague Aphanomyces astaci and competitive displacement of native European species.…”
Section: Introductionmentioning
confidence: 99%
“…Through a combination of large size, broad feeding habitats and high densities attained, their introduction to new habitats can have a significant impact on the aquatic environment (NYSTRÖM and STRAND, 1996;NYSTRÖM, 2002;DORN and WOJDAK, 2004). The introduction of North American crayfish species into Europe has been partially responsible for severe declines in indigenous European species (HENTTONEN and HUNER, 1999;HOLDICH, ROGERS and REYNOLDS, 1999) through a combination of transfer of crayfish plague Aphanomyces astaci and competitive displacement of native European species.…”
Section: Introductionmentioning
confidence: 99%
“…Abrahamsson, 1966;Lorman and Magnuson, 1978;Momot et al, 1978). For example, in a range of North American ponds, crayfish had both direct and indirect community effects on the biomass of zooplankton and phytoplankton assemblages and peak levels of dissolved oxygen, also strong negative effects on macrophyte establishment, metaphyton abundance and composition, gastropod biomass, and the density of bullfrog tadpoles (Dorn and Wojdak, 2004). These and other studies suggest that lakes and ponds with abundant crayfish will be structurally comparatively simple, with few macrophytes and gastropods.…”
Section: Introductionmentioning
confidence: 99%
“…These and other studies suggest that lakes and ponds with abundant crayfish will be structurally comparatively simple, with few macrophytes and gastropods. In such systems some species of amphibians and fish will perform poorly, while other organisms may benefit (Dorn and Wojdak, 2004). Freshwater decapods often coexist with fish in streams and lakes, although other situations where crayfish live, including swamps and temporary wetlands, may not support fish.…”
Section: Introductionmentioning
confidence: 99%
“…Further, most bass and pumpkinseed sunfish concentrate their nests in shallow littoral zones, which make eggs more vulnerable to crayfish predation. In experimental ponds, Dorn and Mittlebach (2004) and Dorn and Wojdak (2004) observed virile crayfish preying heavily on fish eggs and found that a crayfish presence significantly affected the successful reproduction of bluegill sunfish, Lepomis macrochirus Rafinesque, reducing the recruitment of young-of-the-year. Fitzsimons et al (2002) estimated a crayfish (O. virilis) consumption of 82% of the potential egg numbers at lake trout spawning reefs based on both the published literature (Miller et al 1992) and experimental work, concluding that high crayfish density and low egg abundance (<100 eggs m À2 ) may also limit natural recruitment of trout in Lake Ontario.…”
Section: Crayfish Predation On Fishmentioning
confidence: 99%
“…In the temporary ponds of Doñ ana Natural Park, red swamp crayfish had a strong effect on the reproductive success of Bufo calamita (Laurenti), the survival of its embryos being strikingly reduced when they were directly exposed to crayfish (Cruz et al 2006a). Dorn and Wojdak (2004) studied the effects of the virile crayfish, Orconectes virilis (Hagen), on the development and structure of littoral communities in newly established freshwater ponds in south-western Michigan (USA) and found no bullfrog (Rana catesbiana Shaw) tadpoles in any of the crayfish ponds although tadpoles were abundant in the control ponds.…”
Section: Introductionmentioning
confidence: 99%